2018
DOI: 10.3390/en11112946
|View full text |Cite
|
Sign up to set email alerts
|

A Passenger-Oriented Optimization Model for Implementing Energy-Saving Strategies in Railway Contexts

Abstract: Rail and metro systems are characterized by high-performing and environmentally friendly features that make them a crucial factor for driving modal split towards public transport modes, thus reducing private car use and related externalities (such as air and noise pollution, traffic congestion and accidents). Within this framework, the implementation of suitable energy-saving policies, allowing to reduce energy consumption, but, at the same time, preserving timetable stability and passengers’ satisfaction, may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Within this context, the main contribution of the paper consists in advancing the research proposed by [20,31,44], since it analyses eco-driving strategies just in the case of disruption schemes. To this end, the operational parameters of frequency-based systems are first described.…”
Section: The Proposed Methodology For Managing Rolling Stock Unavailamentioning
confidence: 99%
See 1 more Smart Citation
“…Within this context, the main contribution of the paper consists in advancing the research proposed by [20,31,44], since it analyses eco-driving strategies just in the case of disruption schemes. To this end, the operational parameters of frequency-based systems are first described.…”
Section: The Proposed Methodology For Managing Rolling Stock Unavailamentioning
confidence: 99%
“…As widely shown elsewhere (see, for instance, [31,44]), the definition of a frequency-based service consists in determining operational variable values so as to satisfy the following equation:…”
Section: Frequency-based Service Definitionmentioning
confidence: 99%
“…The model optimized the train timetable by controlling the train's headway time and dwell time. D'Acierno and Botte [14] developed an analytical approach to deciding driving strategies. The framework could be used for properly supporting the implementation of eco-driving strategies, from a passenger-oriented perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Two ways were proposed including public control and restriction, as well as public investment in low-emission transport infrastructure. Some literature also focused on the transport behavior, which concluded that major transport policy that could reduce passenger travel levels would be most effective in transport emission cuts [22,[39][40][41].…”
Section: Literature Reviewmentioning
confidence: 99%